The Development of Monograph: Lahan dan Petani as Learning Materials of Agricultural Geography - Aristin, Nevy Farista; Purnomo, Agus (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Improving the quality of learning in the current 4.0 education era can be done through learning materials, one of which is monographs. According to their learning achievements, monographs can increase students' insights based on relevant literature studies and the latest research results following scientific developments. This monograph can support agriculture in Indonesia in the Agricultural Geography. It helps students in applicative ways to understand material related to the use of dryland, especially for students who live where the use of agricultural land is in the form of wetlands or swamps. This study aimed to develop a monograph of Lahan dan Petani as a learning material for agricultural geography using the Sadiman model. In this study, validation tests were carried out by material and media experts who are competent in their fields. The developed monograph was declared feasible as a reference book to support the Agricultural Geography course. It can contribute to education, especially in increasing students' knowledge contextually about dryland agriculture.